2005
DOI: 10.1007/s11187-005-7121-z
|View full text |Cite
|
Sign up to set email alerts
|

Uncertainty and Growth of the Firm

Abstract: Using data from a survey of 1,097 small and medium-sized non-listed Dutch firms we investigate the relation between growth of the firm and uncertainty. We focus on the impact of sales uncertainty on various types of investment. We find that sales uncertainty, measured by the conditional variance, has a mixed impact on various investment decisions. We include an analysis of the relevance of financial structure and firm size on the growth-uncertainty relation. Copyright Springer 2005firm size, uncertainty,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
27
2
6

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 20 publications
5
27
2
6
Order By: Relevance
“…Earlier studies on uncertainty, related to estimating the effects on investment spending, and using very different datasets and estimation procedures, have found similar results related to firm size: for example, Bianco et al (2012), Loungani (1996, 2000), Ghosal (1991), Koetse and Vlist (2006) and Lensink et al (2005). This is reassuring as it points to our results not being an artifact of our specific dataset, methods of estimation, or construction of uncertainty variables.…”
Section: Discussion Of Results and Implicationssupporting
confidence: 83%
See 1 more Smart Citation
“…Earlier studies on uncertainty, related to estimating the effects on investment spending, and using very different datasets and estimation procedures, have found similar results related to firm size: for example, Bianco et al (2012), Loungani (1996, 2000), Ghosal (1991), Koetse and Vlist (2006) and Lensink et al (2005). This is reassuring as it points to our results not being an artifact of our specific dataset, methods of estimation, or construction of uncertainty variables.…”
Section: Discussion Of Results and Implicationssupporting
confidence: 83%
“…Lensink et al (2005) find that uncertainty has a negative impact on the size of investment, no matter what the type of investment is used, and that smaller firms have a lower probability of investing if uncertainty increases. Ghosal (1991) finds that uncertainty negatively affects firms'…”
Section: Empirical Evidencementioning
confidence: 88%
“…This percentage is lower than the average percentage of firms that invest in Latin and Central America which is 56% and in Eastern Europe which is 60%. This pattern of non-investment is different from that documented by Lensink et al (2005) who use a sample of firms located in the Netherlands, out of which about 87% have positive investment. In order to capture a firm's decision to invest we construct a 6 From the sample of firms used in this study, 161 firms reported to not have invested but in fact did report a positive level of investment.…”
Section: Micro Datacontrasting
confidence: 98%
“…Fuss and Vermeulen, 2008;Lensink et al, 2005;Green et al, 2001;Guiso and Parigi, 1999 and see also the literature review by Carruth et al, 2000 and meta-analysis by Koetse et al, 2009). In particular, most evidence on the investment uncertainty relationship in developing countries suggests that uncertainty (as well as irreversibility) has a negative effect on investment.…”
Section: Literature Reviewmentioning
confidence: 97%
“…Lensink et al (2005) find that uncertainty has a negative impact on the size of investment, no matter what the type of investment is used, and that smaller firms have a lower probability of investing if uncertainty increases. Ghosal (1991) finds that uncertainty negatively affects firms' input-mix as measured by the capital-labor ratio, and that larger firms' input-mix appears less affected by uncertainty.…”
Section: Empirical Evidencementioning
confidence: 88%